Transcutaneous electrical acupoint stimulation to prevent dizziness after microvascular decompression for hemifacial spasm: A randomized controlled trial - Yuantao Hou; Hansheng Liang; Cungang Fan; Ruen Liu; Yi Feng (Elsevier, 2024)
Background: Dizziness often occurs after microvascular decompression (MVD), and therapeutic options are limited. The aim of this trial was to determine the potential efficacy of transcutaneous electrical acupoint stimulation (TEAS), against dizziness and its safety in patients undergoing MVD. Methods: Adult patients scheduled to undergo MVD for hemifacial spasm under total intravenous anesthesia were randomized at a 1:1 ratio to receive, after extubation, 30-min TEAS in the mastoid region as well as Fengchi acupoints (GB20) and Neiguan acupoints (PC6) or 30-min sham stimulation. The primary outcome was the incidence of dizziness at 2 h after surgery. Secondary outcomes included dizziness, postoperative nausea and vomiting (PONV) or headache severity, rescue medication, changes in intraocular pressure before and after surgery, length of stay, dizziness symptoms 4 weeks after discharge, and surgical complications. Results: A total of 86 patients (51.9 ± 9.4 years of age; 67 women) were enrolled. One patient (in the TEAS arm) was excluded from analysis due to conversion to sevoflurane anesthesia. The rate of dizziness at 2 h after surgery was 31.0 % (13/42) in the TEAS arm vs. 53.5 % (23/43) in the sham control arm (P = 0.036). TEAS was also associated with significantly lower severity of dizziness, based on a 10-point scale, during the first 24 h after surgery. None of the other secondary efficacy outcomes differed significantly between the two arms. All postoperative complications were Clavien-Dindo grade I or II. The rate of postoperative complications was 21.4 % (9/42) in the TEAS arm vs. 16.3 % (7/43) in the sham control arm (P = 0.544). Conclusions: Compared with sham control, TEAS was associated with a lower incidence of dizziness within 2 h and lower severity of dizziness within 24 h post-operatively, but no improvement in other outcomes, in adult patients undergoing MVD for hemifacial spasm.